Combined immune checkpoint blockade increases CD8+CD28+PD-1+ effector T cells and provides a therapeutic strategy for patients with neuroblastoma. (1st January 2021) - Shirinbak, Soheila; Chan, Randall Y.; Shahani, Shilpa; Muthugounder, Sakunthala; Kennedy, Rebekah; Hung, Long T.; Fernandez, G. Esteban; Hadjidaniel, Michael D.; Moghimi, Babak; Sheard, Michael A.; Epstein, Alan L.; Fabbri, Muller; et al.
ABSTRACT: Immune checkpoint therapy has resulted in minimal clinical response in many pediatric cancers. We sought to understand the influence of immune checkpoint inhibition using anti-PD-1 and anti-CTLA-4 antibodies individually, in combination, and after chemotherapy on immune responses in minimal and established murine neuroblastoma models. We also sought to understand the role of the tumor microenvironment (TME) and PD-L1 expression and their alteration post-chemotherapy in our models and human tissues. PD-L1 expression was enriched in human tumor-associated macrophages and up-regulated after chemotherapy. In a murine minimal disease model, single and dual immune checkpoint blockade promoted tumor rejection, improved survival, and established immune memory with long-term anti-tumor immunity against re-challenge. In an established tumor model, only dual immune checkpoint blockade showed efficacy. Interestingly, dual immune checkpoint therapy distinctly influenced adaptive and innate immune responses, with significant increase in CD8 + CD28 + PD-1 + T cells and inflammatory macrophages (CD11b hi CD11c − F4/80 + Ly6C hi ) in tumor-draining lymph nodes. Adding chemotherapy before immunotherapy provided significant survival benefit for mice with established tumors receiving anti-PD-1 or dual immune checkpoint blockade. Our findings demonstrate anti-PD-1 and anti-CTLA-4 therapy induces a novel subset of effector T cells, and support administration of induction chemotherapy immediately prior to immune checkpoint blockade in children with high-risk neuroblastoma.